Topical problems of Ukraine State Penitentiary Service reforming - Лихова, Софія Яківна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
Scientific review of the monograph of I. G. Bogatyrev "Penitentiary establishments of Ukraine".